UPAYA UNITED NATIONS POPULATION FUND ( UNFPA ) DAN UNITED NATIONS CHILDREN,S FUND ( UNICEF ) DALAM MENGATASI FEMALE GENITAL MUTILATION DI ETHIOPIA TAHUN 2018-2021 - Bella Dwiana Efendi; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study discusses the efforts of UNFPA and UNICEF in overcoming the practice of Female Genital Mutilation in Ethiopia. Female Genital Mutilation (FGM) is a procedure that involves removing part or all of or injuring the external female genitalia for non-medical reasons and has been recognized as a violation of Women's Human Rights. Ethiopia is the country with the highest number of women who have undergone FGM in the East African region. This made UNFPA and UNICEF pay attention to the issue of FGM in Ethiopia. This study uses a qualitative method, with data collection techniques through library research through literature that related to the problem under study. This research uses the perspective of Pluralism and the theory of International Organization. The results of this paper find that UNFPA and UNICEF work together to overcome Female Genital Mutilation in Ethiopia by raising awareness of the dangers of FGM in collaboration with the government, civil society, social movements, religious leaders through a global program, namely the Joint Program on the Elimination of Female Genital Mutilation. Keywords: Female Genital Mutilation, UNFPA, UNICEF, Human Rights, Ethiopia.